2019
DOI: 10.1111/pala.12450
|View full text |Cite
|
Sign up to set email alerts
|

Brachiopod shell thickness links environment and evolution

Abstract: While it is well established that the shapes and sizes of shells are strongly phylogenetically controlled, little is known about the phylogenetic constraints on shell thickness. Yet, shell thickness is likely to be sensitive to environmental fluctuations and has the potential to illuminate environmental perturbations through deep time. Here we systematically quantify the thickness of the anterior brachiopod shell which protects the filtration chamber and is thus considered functionally homologous across higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Balthasar et al . (2020) have shown that the Strophomenata included both thick‐ and thin‐shelled species and had the largest variety of shell thicknesses, which is consistent with the observations above.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Balthasar et al . (2020) have shown that the Strophomenata included both thick‐ and thin‐shelled species and had the largest variety of shell thicknesses, which is consistent with the observations above.…”
Section: Discussionsupporting
confidence: 86%
“…The shell thickness of Ordovician and Silurian brachiopods has been proven to reflect environmental conditions, but also to be under phylogenetic control (Balthasar et al . 2020) and impose functional constraints on the organisms (Leighton 1998). Flow‐channel experiments also indicate that there is a strong relationship between the shell shape and hydrodynamic energy (Shiino 2010; Shiino & Suzuki 2011, 2015; Shiino & Angiolini 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations